1975
DOI: 10.1029/ja080i022p03121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric fields on the daytime high-latitudeEandFregions

Abstract: We have obtained solutions of the coupled continuity, momentum, and energy equations for NO+, O2+, and O+ ions for conditions appropriate to the daytime high‐latitude E and F regions. Owing to the rapid increase of the reaction O+ + N2 → NO+ + N with ion energy, high‐latitude electric fields and consequent E⊥ × B drifts deplete O+ in favor of NO+. For electric field strengths less than about 10 mV m−1 the depletion of O+ is small, and the altitude profiles of ion density are similar to those found at mid‐latit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
176
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(188 citation statements)
references
References 30 publications
12
176
0
Order By: Relevance
“…Structured electron precipitation, as discussed above, would be the most likely cause of the structure in T e ; however, structure in N e could also arise from other factors. In particular, the concentration of sub-auroral plasma that is convected into the cusp region (Lockwood and Carlson, 1992) may vary and/or the fast ion¯ows that raise the ion temperature may also cause decreases in N e because the loss rates of the plasma are enhanced (Schunk et al, 1975). Rodger et al (1994) suggested these velocity-dependant loss rates may be a signi®cant factor in the cusp/cleft ionosphere.…”
Section: The Origin Of Plasma Structure In and Between 630 Nm Cusp/clmentioning
confidence: 99%
“…Structured electron precipitation, as discussed above, would be the most likely cause of the structure in T e ; however, structure in N e could also arise from other factors. In particular, the concentration of sub-auroral plasma that is convected into the cusp region (Lockwood and Carlson, 1992) may vary and/or the fast ion¯ows that raise the ion temperature may also cause decreases in N e because the loss rates of the plasma are enhanced (Schunk et al, 1975). Rodger et al (1994) suggested these velocity-dependant loss rates may be a signi®cant factor in the cusp/cleft ionosphere.…”
Section: The Origin Of Plasma Structure In and Between 630 Nm Cusp/clmentioning
confidence: 99%
“…Intense convection electric fields appear in the expanded auroral oval [e.g., Yeh et al, 1991] and are responsible for density depletion and ionospheric trough formation due to the effects of enhanced recombination [Schunk et al, 1976]. Collis and Haggstrom [1988] have derived an empirical relationship between the trough location and magnetic Kp index on the basis of observations with the European Incoherent Scatter radars, and Rodger et al [1992] presented an overview of the role of ion drift in the formation of the midlatitude and high-latitude trough.…”
Section: Fieldmentioning
confidence: 99%
“…The subauroral ionosphere is not subjected to the precipitationinduced localized ionization enhancements which characterize the auroral oval. Instead, E x B plasma motions advect ionospheric plasma with significantly different characteristics through this region [Foster, 1993], and chemical recombination of ions in the presence of large electric fields [Schunk et al, 1976] reduces plasma density, producing the deep nighttime ionization trough. These disturbance effects are superimposed on the regular diumal cycle of solar production and nighttime decay of the F region, which has both a latitude and a solar cycle variation.…”
Section: Introductionmentioning
confidence: 99%
“…The component of electric field that is responsible for daytime upward ExB drift is eastward during quiet conditions, which decreases during magnetic disturbances at equatorial region results in the reduction of ExB drift and hence increases in positive phase over equatorial region and negative phase over low latitudes [12]. Due to the peculiar magnetic field geometry at low latitude, phenomenon like Joule heating and field-aligned current are not able to produce strong vertical drift as found at high latitudes but their presence, effect the F2 region behaviour via recombination coefficient and this recombination effects depends on the electric field [13]. Thus the increase in the field leads to the depletion of electron concentration that corresponds to the negative phase.…”
Section: Discussionmentioning
confidence: 99%